Whether partial colectomy is oncologically safe for patients with transverse colon cancer: a large population-based study - Guan, Xu (Oncotarget, 2017)
Due to special tumor location and technical difficulty of transverse colon cancer (TCC), partial colectomy (PC) is being widely applied in selected TCC patients, instead of extended hemicolectomy (HC). However, the oncological safety of this less aggressive surgical approach is not well studied. Here, we identified 10344 TCC patients from Surveillance, Epidemiology, and End-Results (SEER) database. The surgical treatment for those patients included PC and HC. Firstly, we compared lymph nodes evaluations between patients treated with HC and PC, including median number of nodes, the rate of nodes ≥ 12 and the rate of node positivity. Then, 5-year cancer specific survival (CSS) was obtained. Kaplan-Meier methods and Cox regression models were performed to assess the correlations between prognostic factors and long-term survival. Despite of less node examined by PC, the rate of node positivity was equal between PC and HC, suggesting node retrieval under PC was adequate to tumor stage. In addition, the 5-year CSS for patients who underwent PC were 67.5%, which was similar to patients who received HC (66.5%). The result after propensity score matching also confirmed the equivalent survival outcome between HC and PC. However, subgroup analyses showed that patients with tumor size ≥ 5 cm could not obtain survival benefit from PC. Furthermore, surgical approach was not considered as independent prognostic factor for TCC patients. Therefore, although PC is a less aggressive surgical approach, it should be a safe and feasible option for selected TCC patients.